DEVELOPING POCKET BOOK AS A MEDIA IN STUDYING GRAMMAR FOR STUDENTS OF MA DAARUL KAROMAH 10th GRADE - Andika Ramadhan; Adi Adi (Universitas Madura, 2023)
This research is motivated by the observation results, that the learning process is in the eyes English lessons at MA Daarul Karomah grade 10 have so far been less effective, because learning is still centered on the teacher and currently the teaching and learning process is teacher only using the lecture method and without using learning media. This study aims to (1) describe the book development procedure pocket book, (2) knowing the validity of the pocket book development, (3) knowing the effectiveness development of pocket books as a media for learning English in class 10 of MA Daarul Karomah. This study uses Research and Development (R&D). This research uses the Borg and Gall model development. This model was developed by Borg and Gall and has 10 stages and is modified using only 6 stages (research and data collection, planning, develop the product, expert validation, product revision and final product). At the Development stage, the Grammar pocket book is assessed for its feasibility by material expert, media expert. Learning media validation results the very valid category was obtained with a percentage of 91% by material experts and 90% by media experts. It can be concluded that research on the development of pocket book as grammar learning media is stated to be very strong whether used as supporting teaching materials.